عقوبة القذف في القانون الجنائي آتيشه بإندونيسيا : دراسة تحليلية - هندوقو، رزقي عزمي (Kulliyah of Islamic Revealed Knowledge and Human Sciences,al-Jami'at al-Islamiyyah al- 'Alamiyyah Maliziya, 2020)
This research purposes of the penalty of Al-Qadzaf in the Criminal Code No. 6 of 2014 in Aceh; wich is Aceh is a special region in Indonesia that has full authority to apply Islamic Laws, and the application of Al-Qadzaf punishment in Aceh was based of two provisions of Articles no. 57 and 58. The researcher relied on the inductive and analytical approaches to review and analyze information regarding the research on the concept of Al-Qadzaf and its punishment in Islamic jurisprudence and the Aceh Law. The most important result of this research is the punishment of Al-Qadzaf and it is implementation in the Sharia Court in Aceh in Indonesia so that can be applied in Indonesian government. According to the applicable Sharia law in Aceh, the implementation of this law is one of the best way to save moeslem's dignity from Al-Qadzaf.